Tibetan Medicine Duoxuekang Capsule Ameliorates High-Altitude Polycythemia Accompanied by Brain Injury - Chen, Ke; Li, Ning; Fan, Fangfang; Geng, ZangJia; Zhao, Kehui; Wang, Jing; Zhang, Yi; Tang, Ce; Wang, Xiaobo; Meng, Xianli (Frontiers in Pharmacology, 2021)
Objective: Duoxuekang (DXK) capsule is an empirical prescription for Tibetan medicine in the treatment of hypobaric hypoxia (HH)-induced brain injury in plateau. This study aimed to investigate the protective effects and underlying molecular mechanisms of DXK on HH induced brain injury. Methods: UPLC-Q-TOF/MS was performed for chemical composition analysis of DXK. The anti-hypoxia and anti-fatigue effects of DXK were evaluated by normobaric hypoxia test, sodium nitrite toxicosis test and weight-loaded swimming test in mice. Simultaneously, SD rats were used for chronic hypobaric hypoxia (CHH) test. The RBC, HGB, HCT and the whole blood viscosity were evaluated. The activities of SOD and MDA of brain, as well as EPO and LDH of kidney were detected using ELISA. H&E staining was employed to observe the pathological morphology in hippocampus and cortex of rats. Furthermore, immunofluorescence and western blot were carried out to detect the proteins expression of Mapk10, RASGRF1, RASA3, Ras and IGF-IR in brain of rats. Besides, BABL/c mice were for acute hypobaric hypoxia (AHH) test. And western blot was employed to detect the protein expression of p-ERK/ERK, p-JNK/JNK and p-p38/p38 in the cerebral cortex of mice. Results: 23 different chemical compositions of DXK were identified by UPLC-Q-TOF/MS. The anti-hypoxia test verified that DXK can prolong the survival time of mice. The anti-fatigue test confirmed that DXK can prolong the swimming time of mice, decrease the level of LDH, and increase hepatic glycogen level. Synchronously, DXK can decrease the levels of RBC, HGB, HCT and the whole blood viscosity under the CHH condition. Besides, DXK can ameliorate CHH-induced brain injury, and decrease the level of EPO and LDH in kidney, reduce MDA and increase SOD in hippocampus. Furthermore, DXK can converse CHH induced marked increase of Mapk10, RASGRF1 and RASA3, and decrease of Ras and IGF-IR. In addition, DXK can suppressed the ratio of p-ERK/ERK, p-JNK/JNK and p-p38/p38 under the AHH condition. Conclusions: Together, the cerebral protection elicited by DXK was due to the decrease of hematological index, suppress EPO and LDH and in oxidative damage by affecting MAPK signaling pathway, and regulating RAS signaling pathway.